Breastfeeding Self Efficacy Ibu Post Seksio Saesarea - Mardiyaningsih, Eko; Purwaningsih, Heni; Galih Widodo, Gipta (Universitas Muhammadiyah Magelang, 2021)
The one factor that causes mothers to stop breastfeeding is low self- efficacy. The lowest breastfeeding self-efficacy causing the mother to stop breastfeeding too quickly even at the beginning after giving birth to the mother breastfeeding her baby. The goal of this study is to determine the scale of Breastfeeding Self Efficacy in mothers with cesarean childbirth. Descriptive research type, sampling technique with purposive sampling with criteria mothers who give birth with cesarean section, do not experience complications after childbirth and are eager to become respondents. This type of research was descriptive with a purposive sampling technique, the criteria were mothers who gave birth by cesarean section, did not experience postpartum complications, and willing to be respondents. The sample in this study was 52. The study used the Breastfeeding Self Efficacy Scale to explore breastfeeding self-efficacy. Data analysis used univariate analysis in the form of frequency and proportion distributions. The results indicated that most respondents who had a high BSE score were the high-risk age group (56.3%), worker (54.2%), tertiary education (62.5%), breastfeeding experience (51.6%), multipara (53.3%). To increase BSE score, it is necessary to promote breastfeeding so that it is hoped that it will increase the duration of exclusive breastfeeding